A survey on panoramic video methods / Mohd Hanif Mohd Ali, Fakhrul Anuar Aziz and Abd Razak Yaakub - Mohd Ali, Mohd Hanif; Aziz, Fakhrul Anuar; Yaakub, Abd Razak (2004)
Panoramic Video (PY) is an enhanced of Panoramic Image (PI) in virtual environment. PV is 360-degree of video where user can control the video sequence (play forward or backward) while PI is create from a 360-degree of image where user can change viewing direction to the left or right. The issues are PI cannot contain any moving object because it will distort and blur the image after stitching it. Stitching is a process to joint seamlessly the images into panoramic image. PI also not as real as PV because it just contains static movement (image) while PV can contain movable objects (video). The purpose of this paper is to compare the three methods to build a panoramic video system and decide the best method to capture 360-degree video without sacrifices the image resolution and quality. The three approaches are Catadioptric System with Perspective Lens (CSPL), Catadioptric System with Orthographic Lens (CSOL) and Multiple Cameras. CSPL uses mirrors and perspective lens to enhance the field of view (FOY). CSOL also uses mirrors but the lens is orthographic. This is because, orthographic lens can simplify the calibration and computation. Multiple Cameras is a method that will use multiple (at least four) Digital Video cameras to capture a 360-degree of video. It is important that each camera view is overlapped each other so it will be reduced the parallax effects. Each of the construction methods, advantages and disadvantages will be revealed and discussed.